2011
DOI: 10.1097/ta.0b013e3181d9a559
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Predictors For Tracheostomy After Cervical Spinal Cord Injury: A National Trauma Databank Review

Abstract: After CSCI, a fifth of patients will require tracheostomy. Intubation on scene or ED, complete CSCI at C1-C4 or C5-C7 levels, ISS≥16, facial fracture, and thoracic trauma were independently associated with the need for tracheostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 19 publications
2
74
1
Order By: Relevance
“…Patients with C-SCI are at increased risk of respiratory failure that may lead to the need for tracheostomy [6,11,13,15,21]. Pulmonary complications are the most common complications in patients with C-SCI [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with C-SCI are at increased risk of respiratory failure that may lead to the need for tracheostomy [6,11,13,15,21]. Pulmonary complications are the most common complications in patients with C-SCI [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with respiratory failure after C-SCI will require intubation and mechanical ventilation, leading to tracheostomy. It has been reported that 21-77 % of patients with C-SCI have undergone tracheostomy [6,11,13,15,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations